Minimal processing for goat milk preservation: Effect of high-pressure processing on its quality - Razali, Muhammad Faiz; Narayanan, Sangitha; Md. Hazmi, Nurul Ashikin; Abdul Karim Shah, Nor Nadiah; Mustapa Kamal, Siti Mazlina; Mohd Fauzi, Noor Akhmazillah; Sulaiman, Alifdalino (Wiley, 2021)
Fresh goat milk spoilt in a short time due to bacterial spoilage. Conventional heat pasteurization can cause nutrient degradation. Hence, high-pressure processing (HPP) is chosen as an alternative. The safety and quality of goat milk processed by HPP (200–600 MPa) and thermal treatment (60–80° C) at 5–15 min were studied. Thirty-day storage study at 25°C and 4°C was carried out as well. Viscosity and total soluble solid of milk were stably retained after HPP treatment and during storage. The refrigerated (4°C) HPP (600 MPa, 10 min, RT) and thermal pasteurized (70°C, 15 min) milk product were observed to be safe up to 10 days with minimal detection of microbial load. In conclusion, HPP followed by the refrigeration of goat milk provides an excellent alternative to traditional thermal pasteurization in terms of shelf life and quality.